CULTURE OF MEMORY OF THE BEGINNING OF SERBIAN MEDICINE (Heritage, 2021)
The study of the history of medicine has developed two approaches: traditional and new, which is more comprehensive. The traditional approach implies the study of important individuals and ideas, the advancement of medicine as a science. This approach is widely accepted in both our and world science. The second, which is much more comprehensive, was initiated by Henry Sigerst with his works, and expanded and came to life in the 1960s and 1970s. The authors of the paper approach the study and presentation of Serbian medieval medicine with the cause-and-effect relationship of health and disease and other medical-historical phenomena and analyze them in a social, cultural and political context. From this point of view, the authors connect the mentioned contests with modern medical problems and approaches. The aim of this paper is to investigate and present the development of Serbian medicine in the Middle Ages, the conditions under which it was formed and developed, as well as the influence of the Serbian state and church on it.The first hospitals were established under the protection of Christian monasteries in the East, but also in the West. In addition to the first hospitals, the ideas of social medicine were born in the Middle Ages, under the influence of Christian thought. All this is a significant contribution to European medicine, the basis without which further development of medical science in the Renaissance would not be possible.The first real hospitals as treatment institutions in medieval Serbia were established in the period from the 13th to the 17th century. The collected historical material indicates the fact that there were nineteen of them. Hospitals were built and arranged on the model of already existing hospitals built on the soil of Byzantium. The monastery hospitals have a significant historical role, because they introduced Serbian medicine into the family of the then European medicine. It should be especially emphasized that Serbia was at the forefront of medicine at that time, because it had special (separate) departments for the treatment of patients with epilepsy and mental illness. A special place is occupied by the monastery hospital Hilandar on the Holy Mountain and the monastery hospital in Studenica.Along with the establishment of hospitals, they are also working on medical education, in the beginning more according to the mentoring principle, so that from the period of King Milutin's rule, the first medical school was established.In the organizational sense, the Serbian monastery hospitals laid the foundations of today's hospital organization, starting from the place for construction, equipment and working conditions, through the election of directors, doctors, medical and non-medical staff, to ethical norms.
Keywords: medieval medicine, development of Serbian hospitals, Hilandarski tipik, Studenički tipik, medical school